2022
DOI: 10.1021/acsomega.1c06860
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior of Environmental Gas Molecules on Pristine and Defective MoSi2N4: Possible Application as Highly Sensitive and Reusable Gas Sensors

Abstract: Inspired by the recent practical application of twodimensional (2D) nanomaterials as gas sensors, catalysts, and materials for waste gas disposal, herein, the adsorption behaviors of environmental gas molecules, including NO, CO, O 2 , CO 2 , NO 2 , H 2 O, H 2 S, and NH 3 , on the 2D pristine and defective MoSi 2 N 4 (MSN) monolayers were systematically investigated using spinpolarized density functional theory (DFT) calculations. Our results reveal that all the gas molecules are physically adsorbed on the MSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…These intriguing properties could enable prom ising applications of MA 2 Z 4 family in nanoelectronic devices such as magnetic tunnel junction, field effect transistors, highly sensitive and reusable gas sensors, etc. [43][44][45][46][47][48][49][50][51] In this paper, we aim to review the recent progress of the novel 2D layered MA 2 Z 4 family, in terms of its structures, ver satile properties, and perspective applications (Figure 2). After introducing the diverse structures in Figure 1, we provide an extensive overview on the versatile properties regarding to mechanics, piezoelectricity, thermal transport, electronics, optics/optoelectronics, and magnetism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intriguing properties could enable prom ising applications of MA 2 Z 4 family in nanoelectronic devices such as magnetic tunnel junction, field effect transistors, highly sensitive and reusable gas sensors, etc. [43][44][45][46][47][48][49][50][51] In this paper, we aim to review the recent progress of the novel 2D layered MA 2 Z 4 family, in terms of its structures, ver satile properties, and perspective applications (Figure 2). After introducing the diverse structures in Figure 1, we provide an extensive overview on the versatile properties regarding to mechanics, piezoelectricity, thermal transport, electronics, optics/optoelectronics, and magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Diagram of monolayer MA 2 Z 4 family in applications of a) Li-Na batteries and b) gas sensors. Reproduced with permissions [49,200]. Copyright 2022, ACS, 2022, Elsevier.…”
mentioning
confidence: 99%
“…The difference in the structural and electronic properties of 2D materials may lead to different adsorption strengths, sensitivity, and selectivity of the resulting nano gas sensors. Choosing specific materials to detect and control target gas molecules can significantly improve the efficiency of the sensors. Previous works have shown that graphene can detect toxic gases, such as CO, NO, NO 2 , and NH 3 molecules. , However, phosphorene has a more significant band gap and electron mobility compared with graphene, which results in a higher affinity for gas molecules. , Its calculated gas adsorption energy and sensor sensitivity are significantly higher than graphene. Further studies have indicated that the gas selectivities of 2D materials may diversify greatly. Among graphene, silicene, phosphorene, and MoS 2 , MoS 2 has the highest adsorption intensity for CO molecule, , phosphorene has the most considerable adsorption energy of 0.86 eV for NO molecule, and silicene is the best for detecting NH 3 and NO 2 molecules …”
Section: Introductionmentioning
confidence: 99%
“…The MoSi 2 N 4 monolayer can be built by intercalating a 2H-MoS 2 -type MoN 2 layer ( n = 3) into an α-InSe-type Si 2 N 2 ( n = 4). Just like the extensive research and application of Mo-based materials in the field of CO 2 reduction, MoSi 2 N 4 has also attracted extensive research attention and reported interesting electronic and catalytic properties, such as promoting the CO 2 reduction reaction (CO 2 RR) efficiency of MoSi 2 N 4 through doping, adsorption, and heterojunction. Therefore, it is of fundamental significance to adopt a new strategy to promote the application of two-dimensional MoSi 2 N 4 in electrocatalytic reactions such as CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%